COVID-19 information center: questions and ways of disseminating reliable information about the pandemic (Research, Society and Development, 2022)
To analyze users' doubts and the means of communication used by CI-COVID-19 to disseminate reliable information about the pandemic, as well as users' satisfaction with the service. Methods: This is a qualitative and quantitative, observational and descriptive study on the implementation of CI-COVID-19. A priori, the channels, means and communication vehicles used were characterized. Then, the content of doubts and fake news was organized by thematic categories and the distribution frequency of each of these categories was determined. In addition, the sources of information used were identified and classified. Finally, the evaluation of users' satisfaction regarding the service provided was analyzed. Results: Over 365 days of activity, CI-COVID-19 used the electronic channel of communication, through visual, audiovisual and auditory means, through social media. During this period, CI-COVID-19 received 330 requests and 610 sources of information were used to answer them, with 48.52% (n=296) classified as primary sources, 20.00% (n=112) as secondary sources and 31.48% (n=192) as tertiary sources. Finally, service users were very satisfied with the work provided. Conclusion: CI-COVID-19 played an important role in combating the infodemic, using various communication channels to spread quality information and having scientific articles as the main source of information about the pandemic caused by the new coronavirus. The high degree of users' satisfaction demonstrates the service provided.